MAIN SOURCES OF POLYSEMY IN PHILOSOPHICAL LANGUAGE - Akhmadullina Alina Ildarovna (Western European Studies, 2025)
Philosophical language is characterized by its conceptual depth, historical layers, and frequent ambiguity. A key linguistic feature in philosophical discourse is polysemy—the presence of multiple related meanings within a single word. This article examines the main sources of polysemy in philosophical language, emphasizing how abstract conceptualization, metaphorical language, historical evolution, and cross-disciplinary borrowing contribute to the semantic richness and complexity of philosophical terms
Keywords: polysemy; philosophy; abstraction; metaphor